Vitamins formed by microorganisms in fermented foods: effects on human vitamin status—a systematic narrative review - Keyvan, Erhan; Adesemoye, Elizabeth; Champomier-Vergès, Marie-Christine; Chanséaume-Bussiere, Emilie; Mardon, Julie; Nikolovska Nedelkoska, Daniela; Palamutoglu, Recep; Russo, Pasquale; Sarand, Inga; Songre-Ouattara, Laurencia; Trajkovska, Biljana; Karakaya, Sibel; et al. (Frontiers in Nutrition, 2025)
IntroductionVitamin deficiencies remain a global health issue, particularly among vulnerable populations. As microorganisms also produce vitamins, this has led to considering Fermented Foods (FF) as potential vehicles for improving vitamin intake. This systematic narrative review, which exclusively relies on human studies, aims to assess the extent to which the consumption of vitamin-rich FF contributes to the maintenance or enhancement of vitamin status in healthy or deficient populations.MethodsA comprehensive literature search (1970–2024) was conducted following the protocols of EFSA and the COST Action PIMENTO to identify interventional and observational studies investigating the influence of FF on biomarkers of vitamin status.ResultsFindings confirm that certain microorganisms, including Bacillus subtilis, Propionibacterium freudenreichii, and some lactic acid bacteria, can increase the levels of vitamins K2, B2, B9, and B12 in FF. Evidence of bioavailability and physiological effects is reported. Notably, folate (vitamin B9) bioavailability was enhanced in some cases following the consumption of Camembert cheese naturally rich in folate, while vitamin K2 status was effectively improved in several studies on natto (fermented soy) and in one study on Jarlsberg cheese. However, evidence for other B vitamins (B1, B2, B3, B5, B6 and B12) is limited or inconsistent, and no human evidence exists for other vitamins. Vitamin bioavailability was found to be significantly influenced by the food matrix, fermentation type, microbial strain, and the form of the vitamin (vitamers). Effects may also be influenced by interactions with gut microbiota, including microbial vitamin synthesis and modulation of absorption.DiscussionDespite encouraging data, there is a lack of well-controlled, large-scale human studies to validate FF as a sustainable strategy to improve vitamin status. Future human studies research should investigate strain-specific effects, food matrix interactions, and long-term health outcomes.